High performance work system and innovative work behaviour: A moderated mediation analysis of knowledge sharing and employee creativity in Nigerian higher education institutions - Azadeh Amoozegar; Oghenekevwe Esohwode; Mohammad Falahat; Hariharan N. Krishnasamy; Temoor Anjum; Valliappan Raju; Mohammad Ali Hasan (PLoS ONE, 2025)
An examination of the literature on human resource management (HRM) and innovation reveals a lack of understanding regarding the mechanism through which HRM and innovation are connected. To address this, the present study proposes a moderated mediation model to elucidate the relationship between HRM, specifically its novel High Performance Work Systems (HPWS), and innovative work behaviour (IWB). This model suggests that employee creativity serves as a mediator between HPWS and innovative work behaviour. Furthermore, the proposed framework incorporates the moderating influence of knowledge sharing on the relationships between HPWS, employee creativity, and innovative work behaviour. The study employed a quantitative methodology with a cross-sectional design, focusing on academic staff at federal and state universities in Nigeria. A self-administered questionnaire was utilised to gather data from 307 employees. The statistical analysis was conducted using SmartPLS 4 software. The findings demonstrated that employee creativity served as a partial mediator in the association between HPWS and IWB, explaining 75.6% of the variance. Furthermore, the study confirmed that knowledge sharing moderated the influence of HPWS on both employee creativity and IWB. The research proposed a novel explanation for the connection between HPWS and innovative work behaviour, addressing the identified gap that potentially involves numerous variables acting as intermediaries or influencing factors. This suggests the need for further exploration to uncover additional potential mechanisms.